A method for grading fruits. - Shamsuddin, Rosnah (2009)
The method of grading fruits involves the fruit being loaded onto a conveyor belt which is motorized and powered by a transformer. The fruit is being transferred along the conveyor belt whereby the conveyor belt has a series mechanical weighing units that includes a weighing plate and mechanical weighing sensors that will measure the weight of fruits. These weighing units will determine the weight of the fruit on the weighing plate. Once the weight of the fruits has been determined, the fruits would be sorted accordingly and classified under the sizes S, M, L, XL and other sizes of fruit weights which does not fall within the predetermined sizes. If the fruit weight falls within the weight range which has been determined on the weighing unit, the weighing sensors will active the pneumatic cylinder into a storage section. If the fruit does not fall within the specified weight range, then it will be conveyed to the next mechanical weighing unit where the same weight determination process is repeated.